2015
DOI: 10.1073/pnas.1510757112
|View full text |Cite
|
Sign up to set email alerts
|

ALDH2(E487K) mutation increases protein turnover and promotes murine hepatocarcinogenesis

Abstract: Mitochondrial aldehyde dehydrogenase 2 (ALDH2) in the liver removes toxic aldehydes including acetaldehyde, an intermediate of ethanol metabolism. Nearly 40% of East Asians inherit an inactive ALDH2*2 variant, which has a lysine-for-glutamate substitution at position 487 (E487K), and show a characteristic alcohol flush reaction after drinking and a higher risk for gastrointestinal cancers. Here we report the characterization of knockin mice in which the ALDH2(E487K) mutation is inserted into the endogenous mur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 42 publications
3
90
2
1
Order By: Relevance
“…Others hypothesize that the ALDH2*2 subunits destabilize NAD + in the ALDH2*1 cofactor binding site [5]. Finally, additional data demonstrate a decrease in protein stability of the ALDH2*2 enzyme in comparison to ALDH2*1 [36].…”
Section: Characterization Of Aldh2*2mentioning
confidence: 93%
See 1 more Smart Citation
“…Others hypothesize that the ALDH2*2 subunits destabilize NAD + in the ALDH2*1 cofactor binding site [5]. Finally, additional data demonstrate a decrease in protein stability of the ALDH2*2 enzyme in comparison to ALDH2*1 [36].…”
Section: Characterization Of Aldh2*2mentioning
confidence: 93%
“…The dominant negative low enzyme activity associated with expression of the ALDH2*2 allele leads to undesirable physiological reactions that challenge a healthy liver following the consumption of alcohol [36]. In an ALDH2*1 homozygous individual, consumption of 0.5 g/kg of ethanol (equivalent to 3-4 drinks in an average weight male) led to a mean blood acetaldehyde concentration of 1.8 μM.…”
Section: Aldh2*2 and Alcohol Dependencementioning
confidence: 99%
“…A previous study in phosphatase and tensin homolog null nonalcoholic steatohepatitis liver tissue isolated from mice revealed that ACSL1 expression is decreased, and is almost non-existent in tumors isolated from these livers (21). A recent study (22) demonstrated that the presence of a specific mutation in ALDH2 (E487 K) led to increased protein turnover and promoted murine hepatocarcinogenesis. The presence of the DnaJ heat shock protein family (Hsp40) member B1-PRKACA chimeric transcript in fibrolamellar HCC suggests that this genetic alteration contributes to tumor pathogenesis (23).…”
Section: Discussionmentioning
confidence: 99%
“…First, two mouse hepatoma models were identified to represent homogeneous pERK + and pERK -tumors. DEN, a chemical carcinogen, can induce hepatoma in mice after injected to 14-day old pups [19], and the tumors found in mice aged over 8 months were all pERK , in which tumorigenesis is driven by continuous hepatocyte turnover and progenitor cell activation [20,21], express no pERK (Figure 2A and 2B). After tumors were visually confirmed and photographed after median laparotomy (Supplementary Figure 2A and 2B), both groups of mice were treated with sorafenib or PBS daily for three weeks after complete recovery from surgery.…”
Section: High Perk Level Correlates With Sorafenibinduced Necrosis Inmentioning
confidence: 99%
“…F/F ; Alb-Cre +/− , for liver tumor in mice were generated as described previously [19,20]. Sorafenib (30 mpk) or PBS was administered by oral gavage daily for 21 consecutive days.…”
Section: Den-induced Model and Genetic Mutant Ddb1mentioning
confidence: 99%